Concomitant Occurrence of Acute Motor Axonal Neuropathy in Systemic Lupus Erythematosus. (25th April 2023) - Lee, Mirim; Lee, Chang Hee; Ko, Jun Young; Kim, Aram
Abstract: Few case reports exist on the association of acute motor axonal neuropathy, a subtype of the Guillain-Barré syndrome (GBS), with systemic lupus erythematosus. Standard therapeutic guidelines for concomitant acute motor axonal neuropathy and systemic lupus erythematosus in the acute phase are not established, and no studies have reported physical medicine and rehabilitation perspective management in the plateau and recovery phases. A 50-yr-old woman with systemic lupus erythematosus presented with upper and lower limb weakness that progressed to an inability to walk. Neurological examination, radiologic evaluation, serologic analysis, and electrodiagnostic study were conducted, and she was diagnosed with acute motor axonal neuropathy. Subsequently, intravenous immunoglobulin therapy was administered. She complained of residual upper and lower extremity weakness and an inability to walk 3 mos after symptom onset. She underwent an intensive inpatient rehabilitation program for 6 wks and showed remarkable recovery in muscle strength and functional status (Berg Balance Scale, modified Barthel index, and Guillain-Barré syndrome disability scale). To our knowledge, this is the first reported case that focused on the functional outcomes after the rehabilitation program in acute motor axonal neuropathy with a history of systemic lupus erythematosus. This case report emphasizes the need for rehabilitation intervention for functional recovery in the plateau and recovery phases.